Modern intellectual invasion(characteristics - warnings) (Journal of the College of Basic Education, 2023)
This study aims to demonstrate the danger of the intellectual invasion on the whole world, as it caused a radical revolution in the lives of Muslims in most Islamic countries, and many of them strayed from the straight path, and many countries became hostages to the intellectual invasion, as it completely destroys and erases the identity of societies.The Islamic nation has become a valuable target for exporting ideas and empowering missionary centers. So that Islamic societies remain a freak, distorted, and lost.Confronting the intellectual invasion is an Islamic necessity, and it is the nation's right to see the sites, and to know the required steps in order to be able to confront this dangerous invasion.This study showed the subject of the intellectual invasion and its dominance and control over the Islamic world, in terms of its concept that it is a human effort exerted by the invaded through destructive ideas towards a nation, and its history, which is its emergence since the time of the prophets, may God’s prayers be upon them, as it showed the most important characteristics that characterize the intellectual invasion. With its superiority over the military invasion being more dangerous than it, and the reasons that led to the Islamic nation falling under the control of the intellectual invasion, and the most important methods used by Westerners to control this nation in several ways that accompany their lives and their fateful entity